The entomopathogenic fungus, Metarhizium anisopliae for the European grapevine moth, Lobesia botrana Den. & Schiff. (Lepidoptera: Tortricidae) and its effect to the phytopathogenic fungus, Botrytis cinerea - Aguilera Sammaritano, Juan Alberto (2018)
The European grapevine moth, Lobesia botrana Den. & Schiff. (Lepidoptera: Tortricidae) and the gray rot fungus(Botrytis cinerea) are two important factors that cause elevated losses of productivity in vineyards globally. TheEuropean grapevine moth is one of the most important pests in vineyards around the world, not only because ofits direct damage to crops, but also due to its association with the gray rot fungus; both organisms are highlydetrimental to the same crop. Currently, there is no effective, economic, and eco-friendly technique that can beapplied for the control of both agents. On the other hand, Metarhizium anisopliae belongs to a diverse group ofentomopathogenic fungi of asexual reproduction and global distribution. Several Metarhizium isolates have beendiscovered causing large epizootics to over 300 insects? species worldwide. In this study, a simple design wasconducted to evaluate the potential of native M. anisopliae isolates as one of biological control agents against L.botrana and as possible growth inhibitors to B. cinerea. Entomopathogenic fungal strains were isolated from aridsoils under vine (Vitis vinifera) culture. Results suggest that the three entomopathogenic strains (CEP413, CEP589,and CEP591) were highly efficient in controlling larval and pupal stages of L. botrana, with mortality rates rangingfrom 81 to 98% (within 4?6 days). Also, growth inhibition over B. cinerea strains resulted in percentages rangedfrom 47 to 64%. Finally, the compatibility of the entomopathogenic strains, with seven commercial fungicides, wasevaluated. The potential of the entomopathogenic fungal strains to act as control agents is discussed.